2020
DOI: 10.1016/j.ejvs.2020.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Early Renal Function Alterations in Renal Branches vs. Renal Fenestrations – A Dynamic Scintigraphy Based Prospective Study

Abstract: This single centre prospective study involved 67 patients treated by fenestrated and branched endovascular aneurysm repair (F/BEVAR) technology, who were divided into two groups depending on the renal bridging configurations (fenestration vs. branch). The renal outcomes were studies with standard laboratory parameters (serum creatinine levels and estimated glomerular filtration rate calculation with the Chronic Kidney Disease Epidemiology Collaboration equation) and with 99m Tc dynamic renal scintigraphy to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…This is important given that SCr will only deviate outside normal value(s) only once at least half of the functioning renal mass has been affected. In their study, Orrico et al 1 reported that the mean total GFR at the three month scintigraphy decreased by 6.0 AE 2.9 mL/min in the fenestration group and by 23.4 AE 6.4 mL/min in the branch group. However, at one year, the decrease in GFR remained stable.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…This is important given that SCr will only deviate outside normal value(s) only once at least half of the functioning renal mass has been affected. In their study, Orrico et al 1 reported that the mean total GFR at the three month scintigraphy decreased by 6.0 AE 2.9 mL/min in the fenestration group and by 23.4 AE 6.4 mL/min in the branch group. However, at one year, the decrease in GFR remained stable.…”
mentioning
confidence: 90%
“…We read with great interest the study by Orrico et al in the present issue. 1 Renal dysfunction after aortic intervention is a common and important complication. 2,3 Early literature used mostly inconsistent or inappropriate reporting criteria, such as absolute deviation in serum creatinine (SCr) levels, which made data interpretation difficult.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Orrico et al showed that use of branches was associated with a greater decrease in the eGFR than use of fenestrations, which was already evident on three month renal scintigraphy and stable at one year, but the evolution and clinical significance of these data still need to be documented. 31 Therefore, although use of fenestrations over branches might be warranted for incorporation of renal arteries based on these preliminary data, it should always be borne in mind that selection of stent graft design is often mandated by the need to accommodate the aortic anatomy at the level of target vessel origin. In fact, durability of both fenestrations and branches after complex EVAR procedures remains a debated issue, 32 even after the introduction of newer generation bridging stent grafts 33e35 and refined assessment of their geometrical configuration, 36e38 and future research should focus on risk prediction models for loss of RA patency that could better inform how to structure adequate follow up protocols.…”
Section: No At Riskmentioning
confidence: 99%